Elaboração, caracterização físico-química e avaliação da capacidade antioxidante de cerveja de trigo adicionada de pseudofruto de caju (anacardium occidenale) e casca de laranja (citrus sinensis) - Pereira, Iana Maria Cristino (2016)
Beer is the beverage obtained by alcoholic fermentation of beer wort formed by drinking water and barley malt, by the action of yeast, with the addition of hops. Among its variations, this is how wheat beer is made. During its preparation, adjuncts can be used as a source of carbohydrate that reduce costs and make it possible to improve physical, chemical and sensory characteristics of the beer. The peel of orange (Citrus sinensis) and the cashew pseudofruit (Anacardium occidentale), currently discarded as industrial by-products, can be reused by having in its constitution interesting features for use in the preparation of beer. In this context, the objective was to develop a wheat beer with the addition of cashew peduncle and orange peel by the craft process. Therefore, an experimental strategy with such raw materials was carried out, with a percentage calculated on malt. The bark concentrations were 0 and 0.6 % (m/m) and cashew, 0, 5 and 10 % (m/m), resulted in six different combinations. The raw materials were characterized by physico-chemical assessment and added to the fermentation phase. The formulations were subjected to low fermentation, maturation and carbonation. Subsequently, they were characterized regarding the total acidity analysis, pH, real, unique and apparent extracts, total solids, alcohol content, reducing sugars, non-reducing and total chemical composition, calorie, phenolic compounds, antioxidant activity, coliforms at 35 ° C and 45 ° C, molds and yeasts. The results showed that the values obtained from the analysis of pH, total acidity and total soluble solids of cashew were within the standard suggested by the legislation for this fruit, as well as the soluble solids content of oranges from which the peels were extracted. Regarding the analysis of beer formulations, all of them presented characteristics within the parameters required by the legislation. Those containing higher levels of cashew demonstrated to be more acidic, with largest percentage of phenolic compounds and antioxidant activity; although, in this last analysis, there was not a significant difference between all formulations containing the cashew pseudofruit compared to the standard, which did not contain byproducts. The orange peel contributed to higher ash content, original and real extract. Although it has antioxidant activity and phenolic compounds, the added bark did not contribute to increase these compounds, perhaps for the low concentration used. The microbiological analysis presented satisfactory results in all formulations, indicating good sanitary conditions and microbiological stability. It is possible to conclude that the use of these raw materials in the preparation of craft beers is feasible and, in addition to reuse organic residues and reduce process costs, it can add important physical and chemical characteristics to the drink, among which, the formulation number six, containing 10% cashew pseudofruit (m/m) and 0.6% orange peel (m/m), presented the most satisfactory results.